Composite separator, secondary battery, and electric device
Patent Information
- Application Number
- CN202380056620.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-20
- Publication Date
- 2025-03-14
AI Technical Summary
The safety and cycle performance of metal secondary batteries are due to the uneven current density of the negative electrode current collector, which leads to the formation of sodium dendrites, affecting the service life and safety of the battery, making it difficult to meet the needs of the new generation of battery systems.
Using a composite isolation film, including an isolation film base material and a conductive coating located on one side of the isolation film base material, by improving the current density of metal ion deposition and reducing overpotential, combined with a ceramic coating to reduce thermal shrinkage and prevent internal short circuits, improve Battery safety and cycle performance.
Through uniform metal ion deposition and reduced sodium dendrite formation, the safety performance and cycle performance of the battery are significantly improved, the risk of internal short circuits and self-discharge are reduced, and the service life of the battery is extended.
Smart Images

Figure CN119631235A_ABST
Abstract
Description
Composite separator, secondary battery and electrical device Technical Field
[0001] The present application relates to the technical field of secondary batteries, and in particular to a composite isolation membrane, a secondary battery, and an electrical device. Background Art
[0002] In recent years, secondary batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as in power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields.
[0003] Metal secondary batteries have attracted considerable attention in recent years due to their advantages, including high theoretical specific capacity of negative electrodes, a wide range of raw materials, and low raw material prices. However, the safety of metal secondary batteries has always been a difficult technical issue to resolve, hindering their widespread application.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a composite isolation membrane, which includes an isolation membrane substrate and a conductive coating located on one side of the isolation membrane substrate, which is beneficial to improving the current density of metal ion deposition on the negative electrode collector so that the metal ions are deposited evenly, and is also beneficial to reducing the overpotential of the battery, further improving metal dendrites, and improving the safety and cycle performance of the battery.
[0006] In a first aspect of the present application, a composite isolation membrane is provided. The composite isolation membrane includes an isolation membrane substrate and a conductive coating located on one side of the isolation membrane substrate.
[0007] By providing a conductive coating on one side of the isolation membrane substrate, the current density of metal ion deposition on the negative electrode current collector can be improved, the overpotential during metal ion deposition can be reduced, the uniformity of metal ion deposition can be improved, the generation of metal dendrites can be reduced, and the safety and cycle performance of the battery can be improved.
[0008] In any embodiment, the composite isolation membrane further comprises a ceramic coating located on at least one side of the isolation membrane substrate, wherein the ceramic coating is located between the isolation membrane substrate and the conductive coating; and / or
[0009] The ceramic coating is located on a side of the isolation film substrate facing away from the conductive coating.
[0010] The composite isolation membrane also includes a ceramic coating, which can effectively reduce the thermal shrinkage of the composite isolation membrane, improve its thermal stability, avoid or reduce internal short circuits caused by shrinkage of the composite isolation membrane, and significantly improve the safety of the battery.
[0011] In any embodiment, the ceramic coating is located between the isolation membrane substrate and the conductive coating, which can further prevent direct contact between the conductive coating and the positive electrode film layer, avoid or reduce the penetration of conductive materials into the isolation membrane substrate, reduce the self-discharge phenomenon of the battery, reduce the risk of internal short circuit of the battery, and improve battery performance.
[0012] In any embodiment, the thickness of the conductive coating is 0.05 μm to 10 μm, and optionally 0.5 μm to 5 μm.
[0013] Controlling the thickness of the conductive coating within an appropriate range can not only improve the uniformity of ion transmission through the conductive coating and reduce the formation of dendrites, but also avoid or reduce the self-discharge phenomenon caused by excessive conductive coating thickness. Further controlling the thickness of the conductive coating to 0.5μm to 5μm will further improve battery performance.
[0014] In any embodiment, the surface density of the conductive coating is 0.01 mg / 1540.25 mm 2 ~15mg / 1540.25mm 2 , optional 0.05mg / 1540.25mm 2 ~8mg / 1540.25mm 2 .
[0015] Controlling the surface density of the conductive coating within a suitable range is beneficial to promoting the uniform transport and deposition of metal ions.
[0016] In any embodiment, the conductive coating comprises a conductive material comprising at least one of a conductive carbon material and a conductive polymer.
[0017] The conductive material in the conductive coating has a certain electron conduction ability, which is beneficial to reducing the overpotential of metal ion deposition, facilitating the uniform deposition of metal ions, further improving metal dendrites, and improving the cycle performance and service life of the battery.
[0018] In any embodiment, the conductive carbon material includes at least one of a zero-dimensional carbon material, a one-dimensional carbon material, and a two-dimensional carbon material, and optionally includes the one-dimensional carbon material.
[0019] In any embodiment, the zero-dimensional carbon material comprises at least one of acetylene black, Super P and Ketjen black;
[0020] The one-dimensional carbon material comprises at least one of carbon nanofibers, carbon nanotubes, carbon nanohorns and carbon nanorods, and optionally comprises carbon nanotubes;
[0021] The two-dimensional carbon material includes at least one of natural graphite and artificial graphite.
[0022] The above conductive materials all have excellent electrical conductivity, which is beneficial to reducing the overpotential of metal ion deposition, so as to facilitate uniform deposition of metal ions and improve the phenomenon of metal dendrites.
[0023] In any embodiment, the thickness of the ceramic coating is 0.05 μm to 10 μm, and optionally 0.5 μm to 3 μm.
[0024] Controlling the ceramic coating within an appropriate thickness range can not only reduce the thermal shrinkage of the composite isolation membrane and improve the safety of the battery, but also avoid or reduce the decrease in energy density of the battery caused by excessive thickness of the ceramic coating.
[0025] In any embodiment, the surface density of the ceramic coating is 0.0001 mg / 1540.25 mm 2 ~0.05mg / 1540.25mm 2 , optional 0.001mg / 1540.25mm 2 ~0.02mg / 1540.25mm 2 .
[0026] Controlling the surface density of the ceramic coating within an appropriate range is beneficial to reducing the thermal shrinkage of the composite isolation membrane, avoiding or reducing internal short circuits, and does not affect the transmission behavior of metal ions.
[0027] In any embodiment, the ceramic coating comprises an inorganic material, and the inorganic material comprises one or more of Al2O3, AlO(OH), SiO2, TiO2, MgO and CaO, and optionally comprises Al2O3.
[0028] The above-mentioned inorganic materials all have excellent thermal stability, which is beneficial to reducing the thermal shrinkage of the composite isolation membrane and improving its performance.
[0029] In any embodiment, the conductive coating and / or the ceramic coating further includes a binder, and the binder includes one or more of polyvinylidene fluoride, sodium hydroxymethyl cellulose, styrene-butadiene rubber, potassium carboxymethyl cellulose, polyacrylate, polyamide, polyimide, polyamide-imide, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene and polyacrylonitrile, and optionally includes polyvinylidene fluoride.
[0030] The above-mentioned adhesives are all conducive to the bonding between the conductive coating / ceramic coating and the isolation membrane substrate or between the conductive coating and the ceramic coating, thereby improving the stability of the composite isolation membrane.
[0031] In any embodiment, the binder in the conductive coating is the same as the binder in the ceramic coating.
[0032] The binder in the conductive coating is the same as the binder in the ceramic coating, which is beneficial to the compatibility between the conductive coating and the ceramic coating, and avoids or reduces further increase in the interface resistance between the conductive coating and the ceramic coating.
[0033] In any embodiment, the mass ratio of the conductive material to the binder in the conductive coating is 4-49.
[0034] By controlling the mass ratio of the conductive material to the binder in the conductive coating within an appropriate range, both the performance and the production cost of the composite isolation membrane can be taken into consideration.
[0035] In any embodiment, the mass ratio of the inorganic material to the binder in the ceramic coating is 4-40.
[0036] By controlling the mass ratio of the inorganic material to the binder in the ceramic coating within an appropriate range, both the performance and the production cost of the composite isolation membrane can be taken into account.
[0037] In any embodiment, the separator substrate comprises one or more of polyethylene, polypropylene, polyester, cellulose, polyimide, polyamide, spandex fiber and aramid fiber, and optionally comprises polyethylene.
[0038] The sources of isolation membrane substrates are wide, and all of the above isolation membrane substrates can be used in conjunction with conductive coatings to improve battery performance.
[0039] In any embodiment, the separator substrate comprises polyethylene, the ceramic coating comprises Al 2 O 3 , and the conductive coating comprises carbon nanotubes.
[0040] The combination of polyethylene, Al2O3 and carbon nanotubes gives the composite isolation membrane excellent performance.
[0041] In any embodiment, in any direction perpendicular to the thickness direction of the composite isolation membrane, the width of the conductive coating is less than the width of the isolation membrane substrate.
[0042] In any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is less than the width of the separator substrate. The separator has a larger width to prevent the conductive coating from contacting the positive electrode film layer, thereby reducing the risk of safety accidents caused by internal short circuits in the battery.
[0043] In any embodiment, in any direction perpendicular to the thickness direction of the composite isolation membrane, the width of the conductive coating is ≤ the width of the ceramic coating ≤ the width of the isolation membrane substrate.
[0044] In any direction perpendicular to the thickness of the composite separator, controlling the width of the conductive coating to be ≤ the width of the ceramic coating ≤ the width of the separator substrate effectively balances the electrochemical performance and safety of the battery. A second aspect of the present application provides a secondary battery comprising a negative electrode sheet and the composite separator described in the first aspect, wherein the conductive coating in the composite separator is located on the negative electrode sheet side.
[0045] The conductive coating is located on the negative electrode side, which helps to improve the current density of the negative electrode collector, reduce the overpotential of metal ion deposition, and improve metal dendrites.
[0046] In any embodiment, the secondary battery is a negative electrode-less sodium secondary battery.
[0047] Anode-free sodium secondary batteries have high energy density.
[0048] In any embodiment, the negative electrode plate includes a negative electrode current collector, and in any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is ≤ the width of the negative electrode current collector and < the width of the separator substrate.
[0049] In any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is controlled to be ≤ the width of the negative electrode current collector < the width of the separator substrate. This not only helps the metal ions to be deposited on the negative electrode current collector after passing through the conductive layer in the composite separator, but also avoids contact between the negative electrode current collector and the conductive coating and the positive electrode film layer, avoiding safety accidents caused by internal short circuits.
[0050] In any embodiment, the secondary battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on a side of the positive electrode current collector facing the composite separator;
[0051] In any direction perpendicular to the thickness direction of the composite separator, the width of the positive electrode film layer is less than the width of the conductive coating layer and less than the width of the separator substrate.
[0052] In any direction perpendicular to the thickness direction of the composite separator, the width of the positive electrode film layer is less than the width of the conductive coating layer and less than the width of the separator substrate. This not only helps the precipitation of metal ions during the charge and discharge process, and then all of them are deposited on the negative electrode current collector after passing through the conductive layer in the composite separator, but also avoids contact between the conductive coating and the positive electrode film layer, avoiding safety accidents caused by internal short circuits.
[0053] In any embodiment, in any direction perpendicular to the thickness direction of the composite isolation membrane, the difference between the width of the conductive coating and the width of the positive electrode film layer is 0 mm to 6 mm, the difference between the width of the negative electrode collector and the width of the conductive coating is 0 to 3 mm, and the difference between the width of the isolation membrane substrate and the width of the negative electrode collector is 1 mm to 9 mm.
[0054] The difference between the width of the conductive coating and the width of the positive electrode film layer, the difference between the width of the negative electrode current collector and the width of the conductive coating, and the difference between the width of the isolation film substrate and the width of the negative electrode current collector are controlled within an appropriate range, taking into account both battery performance and production cost.
[0055] In any embodiment, the composite isolation membrane includes a ceramic coating, and in any direction perpendicular to the thickness direction of the composite isolation membrane, the width of the isolation membrane substrate is equal to the width of the ceramic coating.
[0056] In any direction perpendicular to the thickness direction of the composite isolation membrane, the width of the isolation membrane substrate is controlled to be equal to the width of the ceramic coating, thereby further reducing the thermal shrinkage rate of the composite isolation membrane and avoiding safety accidents caused by internal short circuits.
[0057] A third aspect of the present application provides an electrical device comprising the secondary battery according to the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0058] FIG1 is a schematic diagram of a secondary battery according to an embodiment of the present application;
[0059] FIG2 is an exploded view of the secondary battery according to one embodiment of the present application shown in FIG1 ;
[0060] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application;
[0061] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application;
[0062] FIG5 is an exploded view of the battery pack according to an embodiment of the present application shown in FIG4 ;
[0063] FIG6 is a schematic diagram of an electric device using a secondary battery as a power source according to an embodiment of the present application.
[0064] Description of reference numerals:
[0065] 1 battery pack; 2 upper box; 3 lower box; 4 battery module; 5 secondary battery; 51 shell; 52 electrode assembly; 53 cover plate. DETAILED DESCRIPTION
[0066] Below, embodiments of the composite separator, secondary battery, and electrical device of the present application are described in detail with appropriate reference to the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0067] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0068] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0069] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0070] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), indicating that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0071] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.
[0072] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0073] There are currently many problems with metal batteries. Taking the negative electrode-free sodium battery as an example, during the charging and discharging process, the uneven current density of the negative electrode collector leads to uneven deposition of sodium ions, which easily forms sodium dendrites, seriously affecting the battery's service life and safety, and cannot meet the needs of the new generation of battery systems.
[0074] [Composite isolation film]
[0075] Based on this, the present application provides a composite isolation membrane, which includes an isolation membrane substrate and a conductive coating located on one side of the isolation membrane substrate.
[0076] The conductive coating improves the current density of metal ion deposition on the negative electrode current collector and reduces the overpotential of metal ion deposition, so as to make the metal ion deposition uniform, improve the dendrite phenomenon of the negative electrode, and thus improve the safety and cycle performance of the battery.
[0077] Taking metal batteries as an example, the conductive coating is located on the side of the isolation membrane substrate facing the negative electrode. During the charging process, metal ions first pass through the isolation membrane substrate, then through the conductive coating, and are deposited on the surface of the negative electrode current collector, preferentially filling the tiny gap between the negative electrode current collector and the conductive coating, so that the metal deposition is more compact and the formation of metal dendrites is reduced.
[0078] In some embodiments, the composite isolation membrane further comprises a ceramic coating located on at least one side of the isolation membrane substrate, the ceramic coating being located between the isolation membrane substrate and the conductive coating; and / or the ceramic coating being located on the side of the isolation membrane substrate facing away from the conductive coating.
[0079] In some embodiments, the composite separator includes a ceramic coating positioned between the separator substrate and the conductive coating.
[0080] In some embodiments, the composite separator includes a ceramic coating located on a side of the separator substrate remote from the conductive coating.
[0081] In some embodiments, the composite isolation membrane includes two ceramic coating layers, one ceramic coating layer is located between the isolation membrane substrate and the conductive coating layer, and the other ceramic coating layer is located on the side of the isolation membrane substrate away from the conductive coating layer.
[0082] The composite isolation membrane also includes a ceramic coating, which can effectively reduce the thermal shrinkage of the composite isolation membrane, improve its thermal stability, avoid or reduce internal short circuits caused by shrinkage of the composite isolation membrane, and significantly improve the safety of the battery.
[0083] In some embodiments, the ceramic coating is located between the isolation membrane substrate and the conductive coating, which can further prevent direct contact between the conductive coating and the positive electrode film layer, avoid or reduce the penetration of conductive materials into the isolation membrane substrate, reduce the self-discharge phenomenon of the battery, reduce the risk of internal short circuit of the battery, and improve battery performance.
[0084] In some embodiments, the thickness of the conductive coating is 0.05 μm to 10 μm, and can be 0.5 μm to 5 μm. In some embodiments, the thickness of the conductive coating can be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, or a value in a range consisting of any two of the above points.
[0085] Controlling the thickness of the conductive coating within an appropriate range can not only meet the conductive coating's requirement for uniform dispersion of metal ions, but also avoid or reduce the adverse effects of the conductive coating on the battery.
[0086] Further controlling the thickness of the conductive coating to 0.5 μm to 5 μm is beneficial to further improving the performance of the battery.
[0087] In some embodiments, the conductive coating has an areal density of 0.01 mg / 1540.25 mm 2 ~15mg / 1540.25mm2 , optional 0.05mg / 1540.25mm 2 ~8mg / 1540.25mm 2 In some embodiments, the surface density of the conductive coating may be 0.01 mg / 1540.25 mm 2 、0.05mg / 1540.25mm 2 、0.1mg / 1540.25mm 2 、0.5mg / 1540.25mm 2 、1mg / 1540.25mm 2 、1.5mg / 1540.25mm 2 , 2mg / 1540.25mm 2 , 2.5mg / 1540.25mm 2 、3mg / 1540.25mm 2 、3.5mg / 1540.25mm 2 、4mg / 1540.25mm 2 4.5mg / 1540.25mm 2 、5mg / 1540.25mm 2 、5.5mg / 1540.25mm 2 、6mg / 1540.25mm 2 、6.5mg / 1540.25mm 2 、7mg / 1540.25mm 2 ,7.5mg / 1540.25mm 2 、8mg / 1540.25mm 2 , 9mg / 1540.25mm 2 、10mg / 1540.25mm 2 、11mg / 1540.25mm 2 、12mg / 1540.25mm 2 、13mg / 1540.25mm 2 、14mg / 1540.25mm 2 、15mg / 1540.25mm 2 , or a value in the range formed by any two of the above points.
[0088] The surface density of the conductive coating can be tested by any known method, including but not limited to the following methods. For example, when performing the surface density test, a composite isolation film of a specified area (the composite isolation film only includes the isolation film substrate and the conductive coating) can be taken at room temperature, and a circular hole with an area of 1540.25 mm2 can be punched in the composite isolation film using a punching machine. 2Then use an electronic balance to weigh its mass m1 (unit mg), and then use the same method to punch the isolation membrane substrate (blank isolation membrane substrate), and use an electronic balance to weigh its mass m2 (unit mg), (m1-m2) mg / 1540.25mm 2 is the surface density of the conductive coating.
[0089] Controlling the surface density of the conductive coating within a suitable range is beneficial to promoting the uniform deposition of metal ions while not affecting the transport behavior of metal ions.
[0090] In some embodiments, the conductive coating includes a conductive material including at least one of a conductive carbon material and a conductive polymer.
[0091] In this article, the term "conductive polymer" is also called conductive polymer, which can be divided into structural conductive polymers and composite conductive polymers. Generally, structural polymers refer to polymers whose molecular structure contains conjugated long chain structures. The delocalized π electrons on the double bonds can migrate on the molecular chain to form an electric current, making the polymer structure itself inherently conductive. Composite conductive polymers refer to polymers that are filled with conductive materials (such as carbon black, carbon nanotubes, graphene, metals, etc.) in a polymer matrix (such as polyethylene, polypropylene, polystyrene).
[0092] The conductive material in the conductive coating has a certain electron conduction ability, which is beneficial to reducing the overpotential of metal ion deposition, facilitating the uniform deposition of metal ions, further improving metal dendrites, and improving the cycle performance and service life of the battery.
[0093] In some embodiments, the conductive material comprises a conductive carbon material.
[0094] In some embodiments, the conductive material comprises a conductive polymer.
[0095] In some embodiments, the conductive material includes a conductive carbon material and a conductive polymer.
[0096] In some embodiments, the conductive carbon material includes at least one of a zero-dimensional carbon material, a one-dimensional carbon material, and a two-dimensional carbon material, and optionally includes a one-dimensional carbon material.
[0097] As used herein, the term "zero-dimensional carbon material" refers to a carbon material with dimensions less than or equal to 100 nm in all three dimensions. Examples of zero-dimensional carbon materials include, but are not limited to, one or more of Super P, Ketjen black, acetylene black, carbon nanodots, and fullerenes.
[0098] As used herein, the term "one-dimensional carbon material" refers to a carbon material with two dimensions less than or equal to 100 nm. A one-dimensional carbon material can be considered a line. Examples of one-dimensional carbon materials include, but are not limited to, one or more of carbon nanotubes, carbon nanohorns, carbon nanofibers, and carbon nanorods.
[0099] As used herein, the term "two-dimensional carbon material" refers to a carbon material having a size of 100 nm or less in one dimension, and the two-dimensional carbon material can be considered as a plane. By way of example, the two-dimensional carbon material includes but is not limited to graphene and / or graphyne.
[0100] In some embodiments, the zero-dimensional carbon material includes at least one of acetylene black, Super P, and Ketjen black;
[0101] The one-dimensional carbon material includes at least one of carbon nanofibers, carbon nanotubes, carbon nanohorns, and carbon nanorods, and optionally includes carbon nanotubes;
[0102] The two-dimensional carbon material includes at least one of natural graphite and artificial graphite.
[0103] The above conductive materials all have excellent electrical conductivity, which is beneficial to reducing the overpotential of metal ion deposition, so as to facilitate uniform deposition of metal ions and improve the phenomenon of metal dendrites.
[0104] In some embodiments, the thickness of the ceramic coating is 0.05 μm to 10 μm, and may be 0.5 μm to 3 μm. In some embodiments, the thickness of the conductive coating may be 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm, 5.5 μm, 6 μm, 6.5 μm, 7 μm, 7.5 μm, 8 μm, 8.5 μm, 9 μm, 9.5 μm, 10 μm, or a value in a range consisting of any two of the above.
[0105] Controlling the ceramic coating within an appropriate thickness range can not only reduce the thermal shrinkage of the composite separator and improve battery safety, but also avoid or reduce the adverse effects of excessive ceramic coating thickness on the battery.
[0106] In some embodiments, the areal density of the ceramic coating is 0.0001 mg / 1540.25 mm 2 ~0.05mg / 1540.25mm 2 , optional 0.001mg / 1540.25mm 2 ~0.02mg / 1540.25mm 2 In some embodiments, the areal density of the ceramic coating may be 0.0001 mg / 1540.25 mm 2、0.0005mg / 1540.25mm 2 、0.001mg / 1540.25mm 2 、0.0015mg / 1540.25mm 2 、0.002mg / 1540.25mm 2 、0.0025mg / 1540.25mm 2 、0.003mg / 1540.25mm 2 、0.0035mg / 1540.25mm 2 、0.004mg / 1540.25mm 2 、0.0045mg / 1540.25mm 2 、0.005mg / 1540.25mm 2 、0.01mg / 1540.25mm 2 、0.015mg / 1540.25mm 2 、0.02mg / 1540.25mm 2 、0.025mg / 1540.25mm 2 、0.03mg / 1540.25mm 2 、0.035mg / 1540.25mm 2 、0.04mg / 1540.25mm 2 、0.045mg / 1540.25mm 2 、 0.05mg / 1540.25mm 2 , or a value in the range formed by any two of the above points.
[0107] The surface density of the ceramic coating can be tested by any known method, including but not limited to the following methods. For example, the surface density test of the ceramic coating is as follows: when performing the surface density test, a composite isolation film of a specified area (the composite isolation film includes an isolation film substrate, a ceramic coating, and a conductive coating) can be taken at room temperature, and a punching machine can be used to punch a circular hole in the isolation film substrate coated with the ceramic coating. The area of the circular hole is 1540.25mm. 2 Then use an electronic balance to weigh its mass m3 (unit mg), and then use the same method to punch the composite isolation membrane including only the isolation membrane substrate and the conductive coating, and use an electronic balance to weigh its mass m4 (unit mg), (m3-m4) mg / 1540.25mm 2 is the surface density of the ceramic coating.
[0108] Controlling the surface density of the ceramic coating within an appropriate range is beneficial to reducing the thermal shrinkage of the composite isolation membrane, avoiding or reducing internal short circuits, and does not affect the transmission behavior of metal ions.
[0109] In some embodiments, the ceramic coating comprises an inorganic material including one or more of Al2O3, AlO(OH), SiO2, TiO2, MgO, and CaO, optionally including Al2O3.
[0110] The above-mentioned inorganic materials all have excellent thermal stability, which is beneficial to reducing the thermal shrinkage of the composite isolation membrane and improving its performance.
[0111] In some embodiments, the conductive coating and / or ceramic coating further includes a binder, which includes one or more of polyvinylidene fluoride, sodium hydroxymethyl cellulose, styrene-butadiene rubber, potassium carboxymethyl cellulose, polyacrylate, polyamide, polyimide, polyamideimide, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene and polyacrylonitrile, and optionally includes polyvinylidene fluoride.
[0112] The above-mentioned adhesives are all conducive to the bonding between the conductive coating / ceramic coating and the isolation membrane substrate or between the conductive coating and the ceramic coating, and do not affect the transmission of metal ions.
[0113] In some embodiments, the binder in the conductive coating comprises polyvinylidene fluoride and the binder in the ceramic coating comprises sodium carboxymethyl cellulose. In some embodiments, the binder in the conductive coating comprises polyvinylidene fluoride and the binder in the ceramic coating comprises polyacrylate. In some embodiments, the binder in the conductive coating comprises polyvinylidene fluoride and the binder in the ceramic coating comprises polyvinylidene fluoride.
[0114] In some embodiments, the binder in the conductive coating is the same as the binder in the ceramic coating.
[0115] The binder in the conductive coating is the same as the binder in the ceramic coating, which is beneficial to the compatibility between the conductive coating and the ceramic coating, and avoids or reduces further increase in the interface resistance between the conductive coating and the ceramic coating.
[0116] In some embodiments, the mass ratio of the conductive material to the binder in the conductive coating is 4 to 49. In some embodiments, the mass ratio of the conductive material to the binder in the conductive coating can be 4:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 49:1, or a value in a range consisting of any two of the above points.
[0117] By controlling the mass ratio of the conductive material to the binder in the conductive coating within an appropriate range, both the performance and the production cost of the composite isolation membrane can be taken into consideration.
[0118] In some embodiments, the mass ratio of the inorganic material to the binder in the ceramic coating is 4 to 40. In some embodiments, the mass ratio of the inorganic material to the binder in the ceramic coating can be 4:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, or a value in a range consisting of any two of the foregoing values.
[0119] By controlling the mass ratio of the inorganic material to the binder in the ceramic coating within an appropriate range, both the performance and the production cost of the composite isolation membrane can be taken into account.
[0120] In some embodiments, the separator substrate includes one or more of polyethylene, polypropylene, polyester, cellulose, polyimide, polyamide, spandex fiber, and aramid fiber, and optionally includes polyethylene.
[0121] The sources of isolation membrane substrates are wide, and all of the above isolation membrane substrates can be used in conjunction with conductive coatings to improve battery performance.
[0122] In some embodiments, the separator substrate comprises polyethylene, the ceramic coating comprises Al 2 O 3 , and the conductive coating comprises carbon nanotubes.
[0123] The combination of polyethylene, Al2O3 and carbon nanotubes gives the composite isolation membrane excellent performance.
[0124] In some embodiments, in any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is less than the width of the separator substrate.
[0125] In any direction perpendicular to the thickness direction of the composite isolation membrane, the width of the conductive coating is less than the width of the isolation membrane substrate. The isolation membrane completely blocks the contact between the conductive coating and the positive electrode film layer, preventing the conductive coating from contacting the positive electrode film layer, resulting in an internal short circuit and causing a safety accident.
[0126] In some embodiments, in any direction perpendicular to the thickness direction of the composite isolation film, the width of the conductive coating is ≤ the width of the ceramic coating ≤ the width of the isolation film substrate.
[0127] In some embodiments, in any direction perpendicular to the thickness direction of the composite isolation film, the width of the conductive coating = the width of the ceramic coating ≤ the width of the isolation film substrate.
[0128] In some embodiments, in any direction perpendicular to the thickness direction of the composite isolation film, the width of the conductive coating is ≤ the width of the ceramic coating = the width of the isolation film substrate.
[0129] In some embodiments, in any direction perpendicular to the thickness direction of the composite isolation film, the width of the conductive coating is less than the width of the ceramic coating and less than the width of the isolation film substrate.
[0130] In any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is controlled to be ≤ the width of the ceramic coating ≤ the width of the separator substrate, which can effectively take into account both the electrochemical performance and safety of the battery.
[0131] [Positive electrode]
[0132] The positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer formed on at least a portion of the surface of the positive electrode current collector. The positive electrode active material layer includes a positive electrode active material, which may include at least one of a layered transition metal oxide, a polyanionic compound, and a Prussian blue compound.
[0133] The transition metal in the layered transition metal oxide can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Optionally, the layered transition metal oxide is, for example, NaxMO2, wherein M is one or more of Ti, V, Mn, Co, Ni, Fe, Cr, and Cu, and 0<x≤1.
[0134] Polyanionic compounds can be metal ions, transition metal ions and tetrahedral (YO4) n- A class of compounds with anionic units. The metal ion can be selected from sodium ion, lithium ion, potassium ion, and zinc ion; the transition metal can be selected from at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce; Y can be selected from at least one of P, S, and Si; n represents (YO4) n- valence.
[0135] Prussian blue compounds can be compounds containing sodium ions, transition metal ions, and cyanide ions (CN-). The transition metal can be at least one of Mn, Fe, Ni, Co, Cr, Cu, Ti, Zn, V, Zr, and Ce. Prussian blue compounds are, for example, Na a Me b Me' c (CN)6, wherein Me and Me' are each independently at least one of Ni, Cu, Fe, Mn, Co and Zn, 0<a≤2, 0<b<1, 0<c<1.
[0136] The positive electrode active material layer may further include a conductive agent to improve the conductivity of the positive electrode. The conductive agent may be selected from one or more of Super P, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers.
[0137] The positive electrode active material layer may further include a binder to firmly bond the positive electrode active material and optional conductive agent to the positive electrode current collector. The binder may be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), polyvinyl alcohol (PVA), ethylene-vinyl acetate copolymer (EVA), styrene-butadiene rubber (SBR), carboxymethyl cellulose (CMC), sodium alginate (SA), polymethacrylic acid (PMA), and carboxymethyl chitosan (CMCS).
[0138] The positive electrode current collector can be a conductive carbon sheet, metal foil, carbon-coated metal foil, porous metal plate, or a composite current collector. The conductive carbon material of the conductive carbon sheet can be selected from one or more of Super P, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphite, graphene, and carbon nanofibers. The metal material of the metal foil, carbon-coated metal foil, and porous metal plate can each be independently selected from at least one of copper, aluminum, nickel, and stainless steel. The composite current collector can be a composite of metal foil and a polymer-based film.
[0139] In some embodiments, the positive electrode sheet can be prepared by the following method: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.
[0140] [Negative electrode]
[0141] The negative electrode plate may only include a negative electrode current collector without including a negative electrode active material. The negative electrode plate may also be formed by pre-depositing a metal phase on the negative electrode current collector.
[0142] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil or copper foil may be used as the metal foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base material. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer base material (such as a base material of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0143] [Electrolytes]
[0144] The electrolyte conducts ions between the positive and negative electrodes. This application does not specify the type of electrolyte, and the electrolyte can be selected based on the needs. For example, the electrolyte can be liquid, gel, or solid.
[0145] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0146] In some embodiments, the electrolyte salt may be selected from at least one of sodium hexafluorophosphate, sodium bis(fluorosulfonyl)imide, sodium bis(trifluoromethanesulfonyl)imide, sodium trifluoromethanesulfonate, sodium tetrafluoroborate, sodium difluorophosphate, sodium perchlorate, and sodium chloride.
[0147] In some embodiments, the electrolyte contains an ester solvent, and the ester solvent contains at least one selected from ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, and fluoroethylene carbonate.
[0148] In some embodiments, the electrolyte contains an ether solvent, and the ether solvent includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, 1,3-dioxolane, tetrahydrofuran, methyltetrahydrofuran, diphenyl ether and crown ether, and optionally includes one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether.
[0149] Ether solvents possess superior molecular anti-reduction properties, promoting the formation of a stable solid electrolyte interface on the sodium metal surface and reducing side reactions during battery cycling. The combination of a composite separator and an ether solvent simultaneously protects the sodium metal phase in the negative electrode through the polymer coating and stabilizes the formation of a solid electrolyte interface, significantly reducing side reactions and improving battery performance. Ether solvents including one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, diethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether can further enhance the battery's cycling and storage performance.
[0150] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, and additives that improve battery high or low temperature performance.
[0151] [Secondary battery]
[0152] A secondary battery includes a negative electrode sheet and a composite separator in some embodiments, wherein the conductive coating in the composite separator is located on the negative electrode sheet side.
[0153] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape. For example, FIG1 is an example of a square-structured battery cell 5 , and FIG2 is an exploded view of the battery cell 5 .
[0154] In some embodiments, the secondary battery further includes an electrolyte.
[0155] In some embodiments, the secondary battery is a sodium secondary battery.
[0156] The negative electrode materials of sodium secondary batteries include sodium metal and its alloys. The composite separator provided in this application can effectively improve the uniformity of sodium ion deposition at the negative electrode and enhance battery safety.
[0157] In some embodiments, the secondary battery is a negative electrode-less sodium secondary battery.
[0158] A negative electrode-free sodium secondary battery refers to a battery that does not actively set a negative electrode active material layer on the negative electrode side during the battery manufacturing process. For example, during the battery manufacturing process, a sodium metal or carbonaceous active material layer is not set at the negative electrode through coating or deposition to form a negative electrode active material layer. During the first charge, sodium ions obtain electrons on the anode side and metallic sodium is deposited on the surface of the current collector to form a sodium metal phase. During discharge, metallic sodium can be converted into sodium ions and return to the positive electrode, realizing cyclic charge and discharge. Compared with other sodium secondary batteries, negative electrode-free sodium secondary batteries can achieve higher energy density due to the lack of a negative electrode active material layer. Moreover, while maintaining the high electrochemical performance of the battery, it can shorten the battery production cycle, reduce the battery manufacturing cost, and greatly improve production efficiency.
[0159] In some embodiments, to improve battery performance, the negative electrode side of a negative electrode-free sodium secondary battery may be provided with some conventional negative electrode active materials, such as carbonaceous materials, metal oxides, and alloys. Although these materials have a certain capacity, due to their relatively small amount, they are not used as the primary negative electrode active material in the battery and do not form a negative electrode active material layer that performs a sodium intercalation function. Therefore, a sodium secondary battery constructed in this manner can still be considered a negative electrode-free sodium secondary battery.
[0160] In some embodiments, the CB value of the negative electrode-free sodium secondary battery is less than or equal to 0.1.
[0161] The CB value is the capacity per unit area of the negative electrode in a secondary battery divided by the capacity per unit area of the positive electrode. Since a battery without a negative electrode contains no or only a small amount of negative electrode active material, the capacity per unit area of the negative electrode is relatively small, and the CB value of a secondary battery is less than or equal to 0.1.
[0162] In some embodiments, the negative electrode sheet includes a negative current collector, and in any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is ≤ the width of the negative current collector < the width of the separator substrate.
[0163] In some embodiments, in any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating = the width of the negative electrode current collector < the width of the separator substrate.
[0164] In some embodiments, in any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is less than the width of the negative electrode current collector and less than the width of the separator substrate.
[0165] In any direction perpendicular to the thickness direction of the composite separator, the width of the conductive coating is controlled to be ≤ the width of the negative electrode current collector < the width of the separator substrate. This not only helps the metal ions to be deposited on the negative electrode current collector after passing through the conductive layer in the composite separator, but also avoids contact between the negative electrode current collector and the conductive coating and the positive electrode film layer, avoiding safety accidents caused by internal short circuits.
[0166] In some embodiments, the secondary battery further comprises a positive electrode sheet, the positive electrode sheet comprising a positive electrode current collector and a positive electrode film layer located on a side of the positive electrode current collector facing the composite separator;
[0167] In any direction perpendicular to the thickness direction of the composite separator, the width of the positive electrode film layer is less than the width of the conductive coating layer and less than the width of the separator substrate.
[0168] In any direction perpendicular to the thickness direction of the composite separator, the width of the positive electrode film layer is less than the width of the conductive coating layer and less than the width of the separator substrate. This not only helps the precipitation of metal ions during the charge and discharge process, and then all of them are deposited on the negative electrode current collector after passing through the conductive layer in the composite separator, but also avoids contact between the conductive coating and the positive electrode film layer, avoiding safety accidents caused by internal short circuits.
[0169] In some embodiments, in any direction perpendicular to the thickness direction of the composite isolation membrane, the difference between the width of the conductive coating and the width of the positive electrode film layer is 0 mm to 6 mm, the difference between the width of the negative electrode collector and the width of the conductive coating is 0 to 3 mm, and the difference between the width of the isolation membrane substrate and the width of the negative electrode collector is 1 mm to 9 mm.
[0170] In some embodiments, in any direction perpendicular to the thickness direction of the composite separator, the difference between the width of the conductive coating and the width of the positive electrode film layer can be selected as 0, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, or a value in the range consisting of any two of the above points, the difference between the width of the negative electrode collector and the width of the conductive coating is 0, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, or a value in the range consisting of any two of the above points, and the difference between the width of the separator substrate and the width of the negative electrode collector is 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm, 4 mm, 4.5 mm, 5 mm, 5.5 mm, 6 mm, 6.5 mm, 7 mm, 7.5 mm, 8 mm, 8.5 mm, 9 mm, or a value in the range consisting of any two of the above points.
[0171] The difference between the width of the conductive coating and the width of the positive electrode film layer, the difference between the width of the negative electrode current collector and the width of the conductive coating, and the difference between the width of the isolation film substrate and the width of the negative electrode current collector are controlled within an appropriate range, taking into account both battery performance and production cost.
[0172] In some embodiments, the composite isolation membrane includes a ceramic coating, and in any direction perpendicular to the thickness direction of the composite isolation membrane, the width of the isolation membrane substrate is equal to the width of the ceramic coating.
[0173] In any direction perpendicular to the thickness direction of the composite isolation membrane, the width of the isolation membrane substrate is controlled to be equal to the width of the ceramic coating, thereby further reducing the thermal shrinkage rate of the composite isolation membrane and avoiding safety accidents caused by internal short circuits.
[0174] In some embodiments, referring to FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the separator can be formed into an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, and those skilled in the art can select according to specific actual needs.
[0175] In some embodiments, secondary batteries can be assembled into a battery module. The number of secondary batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art according to the application and capacity of the battery module.
[0176] Figure 3 shows an example battery module 4. Referring to Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0177] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0178] In some embodiments, the battery modules described above may be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0179] Figures 4 and 5 illustrate an example battery pack 1. Referring to Figures 4 and 5 , the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 can be positioned over the lower case 3 to form an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0180] [Electrical devices]
[0181] In one embodiment of the present application, an electric device is provided, comprising at least one of a secondary battery according to any embodiment, a battery module according to any embodiment, or a battery pack according to any embodiment.
[0182] The electrical device includes at least one of the secondary batteries, battery modules, or battery packs provided in this application. The secondary batteries, battery modules, or battery packs can be used as power sources for the electrical device, or as energy storage units for the electrical device. The electrical device may include mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc., but is not limited thereto.
[0183] As an electrical device, a secondary battery, a battery module or a battery pack can be selected according to its usage requirements.
[0184] Figure 6 shows an example of an electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of the secondary battery, a battery pack or battery module can be used.
[0185] Another example device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is generally required to be lightweight and thin, and may use a secondary battery as a power source.
[0186] 1. Preparation method
[0187] Example
[0188] Below, the embodiment of the present application is described. The embodiment described below is exemplary and is only used to explain the present application, and is not to be construed as limiting the present application. Where specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. Reagents or instruments used that do not specify the manufacturer are conventional products that can be obtained commercially.
[0189] Example 1
[0190] 1) Preparation of composite isolation membrane
[0191] Conductive carbon nanotubes and polyvinylidene fluoride (PVDF), a first binder, were dissolved in N-methyl-2-pyrrolidone at a mass ratio of 10:1 to form a conductive slurry. This slurry was then extrusion-coated onto one side of a polyethylene separator substrate to form a conductive coating. After coating, the coating was dried and slit to form a composite separator. The difference between the width of the separator substrate and the width of the conductive coating in any direction perpendicular to the thickness of the composite separator was 6 mm.
[0192] 2) Preparation of positive electrode sheet
[0193] 3wt% polyvinylidene fluoride binder is fully dissolved in N-methyl-2-pyrrolidone (NMP), and then 3.0wt% conductive carbon black and 94wt% Na4Fe3(PO4)2P2O7 positive electrode active material are added and stirred to obtain a positive electrode slurry. The slurry is evenly coated on the surface of the current collector aluminum foil to prepare a positive electrode film layer, and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet is rolled and punched to obtain a positive electrode sheet. In any direction perpendicular to the thickness of the composite separator, the difference between the width of the conductive coating and the width of the positive electrode film layer is 3mm.
[0194] 3) Preparation of negative electrode sheet
[0195] Aluminum foil was used as the negative electrode current collector for slitting and die-cutting to produce negative electrode sheets without a negative electrode structure. The difference between the width of the separator substrate and the width of the negative electrode current collector in any direction perpendicular to the thickness of the composite separator was 6 mm.
[0196] 4) Electrolyte
[0197] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 0.8 mol / L.
[0198] 5) Preparation of batteries
[0199] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the separator positioned between the positive and negative electrodes to provide insulation, and the conductive coating of the composite separator facing the negative electrode sheet. Tabs were welded to the bare cell, which was then placed in an aluminum shell and baked at 80°C to remove water. The electrolyte was then injected and sealed to produce an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium secondary battery product of Example 1.
[0200] Example 2
[0201] 1) Preparation of composite isolation membrane
[0202] The inorganic material Al2O3 and the secondary binder polyvinylidene fluoride were dissolved in a solvent, N-methyl-2-pyrrolidone, at a mass ratio of 10:1 to produce a ceramic slurry. The ceramic slurry was then extrusion-coated onto one surface of a polyethylene separator substrate to form a ceramic coating. After coating, the coating was dried and slit to produce a composite separator precursor.
[0203] The conductive material, carbon nanotubes, and the first binder, polyvinylidene fluoride, were dissolved in a solvent, N-methyl-2-pyrrolidone, at a mass ratio of 10:1 to form a conductive material slurry. This conductive material slurry was then extrusion-coated onto the upper surface of the ceramic coating in the composite separator precursor to form a conductive coating (the ceramic coating was positioned between the separator substrate and the conductive coating). After coating, the composite separator was dried and slit to form the composite separator. In any direction perpendicular to the thickness of the composite separator, the difference between the width of the separator substrate and the width of the conductive coating was 6 mm, and the width of the separator substrate was equal to the width of the ceramic coating.
[0204] 2) Preparation of positive electrode sheet
[0205] 3wt% polyvinylidene fluoride binder is fully dissolved in N-methyl-2-pyrrolidone (NMP), and then 3.0wt% conductive carbon black and 94wt% Na4Fe3(PO4)2P2O7 positive electrode active material are added and stirred to obtain a positive electrode slurry. The slurry is evenly coated on the surface of the current collector aluminum foil to prepare a positive electrode film layer, and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet is rolled and punched to obtain a positive electrode sheet. In any direction perpendicular to the thickness of the composite separator, the difference between the width of the conductive coating and the width of the positive electrode film layer is 3mm.
[0206] 3) Preparation of negative electrode sheet
[0207] Aluminum foil was used as the negative electrode current collector for slitting and die-cutting to produce negative electrode sheets without a negative electrode structure. The difference between the width of the separator substrate and the width of the negative electrode current collector in any direction perpendicular to the thickness of the composite separator was 6 mm.
[0208] 4) Electrolyte
[0209] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 0.8 mol / L.
[0210] 5) Preparation of batteries
[0211] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the composite separator positioned between the positive and negative electrodes to act as an insulator, and the conductive coating of the composite separator facing the negative electrode sheet. Tabs were welded to the bare cell, which was then placed in an aluminum shell and baked at 80°C to remove water. The electrolyte was then injected and sealed to produce an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium secondary battery product of Example 2.
[0212] Examples 3 to 14
[0213] The batteries of Examples 3 to 14 were prepared in a similar manner to the battery of Example 2, but the preparation parameters of the composite separator and the secondary battery were adjusted. The specific parameters are shown in Table 1.
[0214] Example 15
[0215] 1) Preparation of composite isolation membrane
[0216] The inorganic material Al2O3 and the secondary binder polyvinylidene fluoride were dissolved in a solvent, N-methyl-2-pyrrolidone, at a mass ratio of 10:1 to form a ceramic slurry. The ceramic slurry was then extrusion-coated onto one surface of a polyethylene separator substrate to form a ceramic coating. After coating, the coating was dried and slit to obtain a composite separator precursor.
[0217] Conductive carbon nanotubes and polyvinylidene fluoride (PVDF), a first binder, were dissolved in a solvent, N-methyl-2-pyrrolidone, at a mass ratio of 10:1 to form a conductive material slurry. This slurry was then extrusion-coated onto the other surface of the insulating membrane substrate in the composite insulating membrane precursor to form a conductive coating (the ceramic coating and the conductive coating were located on either side of the insulating membrane substrate, respectively). After coating, the composite insulating membrane was dried and slit to form the insulating membrane. In any direction perpendicular to the thickness of the composite insulating membrane, the difference between the width of the insulating membrane substrate and the width of the conductive coating was 6 mm, and the width of the insulating membrane substrate was equal to the width of the ceramic coating.
[0218] 2) Preparation of positive electrode sheet
[0219] 3wt% polyvinylidene fluoride binder is fully dissolved in N-methyl-2-pyrrolidone (NMP), and then 3.0wt% conductive carbon black and 94wt% Na4Fe3(PO4)2P2O7 positive electrode active material are added and stirred to obtain a positive electrode slurry. The slurry is evenly coated on the surface of the current collector aluminum foil to prepare a positive electrode film layer, and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet is rolled and punched to obtain a positive electrode sheet. In any direction perpendicular to the thickness of the composite separator, the difference between the width of the conductive coating and the width of the positive electrode film layer is 3mm.
[0220] 3) Preparation of negative electrode sheet
[0221] Aluminum foil was used as the negative electrode current collector for slitting and die-cutting to produce negative electrode sheets without a negative electrode structure. The difference between the width of the separator substrate and the width of the negative electrode current collector in any direction perpendicular to the thickness of the composite separator was 6 mm.
[0222] 4) Electrolyte
[0223] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 0.8 mol / L.
[0224] 5) Preparation of batteries
[0225] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the composite separator positioned between the positive and negative electrodes to act as an insulator. The conductive coating in the composite separator faced the negative electrode sheet, while the ceramic coating in the composite separator faced the positive electrode sheet. Tabs were welded to the bare cell and placed in an aluminum shell. The shell was baked at 80°C to remove water, and then electrolyte was injected and sealed to obtain an uncharged battery. The uncharged battery then underwent the following steps: static standing, hot and cold pressing, formation, shaping, and capacity testing to obtain the negative-electrode-free sodium secondary battery product of Example 15.
[0226] Example 16
[0227] 1) Preparation of composite isolation membrane
[0228] The inorganic material Al2O3 and the secondary binder polyvinylidene fluoride were dissolved in a solvent, N-methyl-2-pyrrolidone, at a mass ratio of 10:1 to form a ceramic slurry. This slurry was then extrusion-coated onto both sides of a polyethylene separator substrate to form a ceramic coating. The coating was then dried and slit to produce a composite separator precursor.
[0229] Conductive material carbon nanotubes and a first binder polyvinylidene fluoride were dissolved in a solvent N-methyl-2-pyrrolidone at a mass ratio of 10:1 to obtain a conductive material slurry. The conductive material slurry was extrusion-coated onto either side of the ceramic coating in the composite isolation membrane precursor to prepare a conductive coating. After coating, the conductive coating was dried and cut to obtain a composite isolation membrane. The thickness of the ceramic coating on both sides of the polyethylene isolation membrane substrate was equal, with a single-layer ceramic coating thickness of 0.75 μm and a surface density of 0.003 mg / 1540.25 mm 2 The thickness of the conductive coating is 2 μm, and the surface density of the conductive coating is 2.622 mg / 1540.25 mm 2 The thermal shrinkage rate of the composite isolation membrane is 0.3. In any direction perpendicular to the thickness direction of the composite isolation membrane, the difference between the width of the isolation membrane substrate and the width of the conductive coating is 6 mm, and the width of the isolation membrane substrate is equal to the width of the ceramic coating.
[0230] 2) Preparation of positive electrode sheet
[0231] 3wt% polyvinylidene fluoride binder is fully dissolved in N-methyl-2-pyrrolidone (NMP), and then 3.0wt% conductive carbon black and 94wt% Na4Fe3(PO4)2P2O7 positive electrode active material are added and stirred to obtain a positive electrode slurry. The slurry is evenly coated on the surface of the current collector aluminum foil to prepare a positive electrode film layer, and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet is rolled and punched to obtain a positive electrode sheet. In any direction perpendicular to the thickness of the composite separator, the difference between the width of the conductive coating and the width of the positive electrode film layer is 3mm.
[0232] 3) Preparation of negative electrode sheet
[0233] Aluminum foil was used as the negative electrode current collector for slitting and die-cutting to produce negative electrode sheets without a negative electrode structure. The difference between the width of the separator substrate and the width of the negative electrode current collector in any direction perpendicular to the thickness of the composite separator was 6 mm.
[0234] 4) Electrolyte
[0235] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 0.8 mol / L.
[0236] 5) Preparation of batteries
[0237] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the composite separator positioned between the positive and negative electrodes to provide isolation, and the conductive coating within the composite separator facing the negative electrode sheet. Tabs were welded to the bare cell, which was then placed in an aluminum case and baked at 80°C to remove water. The electrolyte was then injected and sealed to produce an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium secondary battery product of Example 16.
[0238] Comparative Example 1
[0239] The battery preparation method in Comparative Example 1 is basically similar to that in Example 1, but the composite isolation membrane only includes an isolation membrane substrate, and does not include a conductive coating and a ceramic coating. The specific parameters are shown in Table 1.
[0240] Comparative Example 2
[0241] 1) Preparation of composite isolation membrane
[0242] The inorganic material Al2O3 and the second binder polyvinylidene fluoride are dissolved in the solvent N-methyl-2-pyrrolidone in a mass ratio of 10:1 to obtain a ceramic material slurry. The ceramic material slurry is extrusion-coated on one side of the polyethylene isolation membrane substrate to prepare a ceramic coating (the ceramic coating is located on either side of the isolation membrane substrate). After coating, it is dried and cut to obtain a composite isolation membrane. The thickness of the ceramic coating is 1.5μm and the surface density of the ceramic coating is 0.003mg / 1540.25mm 2 The thermal shrinkage rate of the composite isolation membrane is 0.4, and the width of the isolation membrane substrate is equal to the width of the ceramic coating in any direction perpendicular to the thickness direction of the composite isolation membrane.
[0243] 2) Preparation of positive electrode sheet
[0244] 3wt% polyvinylidene fluoride binder is fully dissolved in N-methyl-2-pyrrolidone (NMP), and then 3.0wt% conductive carbon black and 94wt% Na4Fe3(PO4)2P2O7 positive electrode active material are added and stirred to obtain a positive electrode slurry. The slurry is evenly coated on the surface of the current collector aluminum foil to prepare a positive electrode film layer, and then transferred to a vacuum drying oven for complete drying. The dried electrode sheet is rolled and punched to obtain a positive electrode sheet. In any direction perpendicular to the thickness of the composite separator, the difference between the width of the separator substrate and the width of the positive electrode film layer is 9mm.
[0245] 3) Preparation of negative electrode sheet
[0246] Aluminum foil was used as the negative electrode current collector for slitting and die-cutting to produce negative electrode sheets without a negative electrode structure. The difference between the width of the separator substrate and the width of the negative electrode current collector in any direction perpendicular to the thickness of the composite separator was 6 mm.
[0247] 4) Electrolyte
[0248] In an argon atmosphere glove box (H2O<0.1ppm, O2<0.1ppm), sodium hexafluorophosphate NaPF6 was dissolved in an organic solvent, ethylene glycol dimethyl ether (DME), and stirred evenly to obtain an electrolyte with a sodium salt concentration of 0.8 mol / L.
[0249] 5) Preparation of batteries
[0250] The positive electrode sheet, composite separator, and negative electrode sheet were stacked in order, with the composite separator positioned between the positive and negative electrodes to provide insulation, and the ceramic coating within the composite separator facing the negative electrode sheet. Tabs were welded to the bare cell, which was then placed in an aluminum casing and baked at 80°C to remove moisture. The electrolyte was then injected and sealed to produce an uncharged battery. The uncharged battery then underwent a series of steps, including resting, hot and cold pressing, formation, shaping, and capacity testing, to obtain the negative-electrode-free sodium secondary battery product of Comparative Example 2.
[0251] 2. Performance Testing
[0252] 1. Composite isolation membrane performance test
[0253] 1) Thermal shrinkage test
[0254] Take a 20cm long composite insulation film and spread it flat between two glass plates. Place the glass plates with the insulation film at 110°C for 7 hours. Then remove the composite insulation film and measure its length (C1 (cm)). Thermal shrinkage = (20 - C1) / 20.
[0255] 2) Surface density test
[0256] Conductive coating surface density test: When conducting the surface density test, take a composite isolation film of a specified area at room temperature (the composite isolation film only includes the isolation film substrate and the conductive coating), and use a punching machine to punch a circular hole on the composite isolation film. The area of the circular hole is 1540.25mm 2 Then use an electronic balance to weigh its mass m1 (unit mg), and then use the same method to punch the isolation film substrate (blank isolation film substrate), and use an electronic balance to weigh its mass m2 (unit mg), and finally use (m1-m2) as the surface density of the conductive coating (unit mg / 1540.25mm 2 ).
[0257] Surface density test of ceramic coating: When conducting the surface density test, take a composite isolation film of a specified area at room temperature (the composite isolation film includes an isolation film substrate, ceramic coating and conductive coating), and use a punching machine to punch a circular hole on the isolation film substrate coated with ceramic coating. The area of the circular hole is 1540.25mm 2 Then use an electronic balance to weigh its mass m3 (unit mg). Then use the same method to punch the composite isolation membrane including only the isolation membrane substrate and the conductive coating, and use an electronic balance to weigh its mass m4 (unit mg). Finally, (m3-m4) is used as the surface density of the ceramic coating (unit mg / 1540.25mm 2 )
[0258] 2. Battery performance test
[0259] 1) Overpotential test
[0260] The overpotential test process is as follows: at 25°C, the battery is charged to 100 μA at a constant current of 0.1C, and the most negative potential obtained during the process is recorded as the overpotential.
[0261] 2) Self-discharge test
[0262] The self-discharge test procedure was as follows: the prepared battery was allowed to rest for 30 minutes at 25°C, then charged at a constant current of 0.33C to 3.2V. It was then charged at a constant voltage of 3.2V until the current dropped to 0.05C. The battery was then allowed to rest for 24 hours and then tested for its open-circuit voltage (V1). After 48 hours, the open-circuit voltage (V2) was measured. Self-discharge = (V1 - V2) / 48. The testing procedures for the comparative example and other examples were the same as above.
[0263] 3) Cyclic performance test
[0264] The cycle performance test process is as follows: at 25 ° C, the prepared battery is allowed to stand for 30 minutes, then discharged at a constant current of 0.33C to 3.65V, then charged at a constant voltage of 3.65V until the current drops to 0.05C, and after standing for 1 hour, discharged at a constant current of 0.33C to 2.5V to obtain the initial capacity (C0); after standing for 1 hour, it is charged at a constant current of 0.33C to 3.65V, then charged at a constant voltage of 3.65V until the current drops to 0.05C, and after standing for 1 hour, discharged at a constant current of 0.33C to 2.5V to obtain the process capacity (C1). The above steps are repeated for the same battery, and the process capacity (Cn) of the battery after the nth cycle is recorded at the same time, until Cn / C1=80%, and the number of cycles is recorded. The test process of the comparative example and other embodiments is the same as above.
[0265] 4) Sodium dendrite test
[0266] After n cycles, the battery was disassembled in an argon atmosphere glove box (H2O <0.1ppm, O2 <0.1ppm), and the surface morphology of the negative electrode was visually observed to determine whether sodium dendrites had formed. A negative electrode with no white spots was considered to have no sodium dendrites, a negative electrode with sporadic white spots was considered to have mild sodium dendrites, and a negative electrode with dense white spots was considered to have severe sodium dendrites. The test procedures for the comparative example and other examples were the same as above.
[0267] 3. Analysis of test results of various embodiments and comparative examples
[0268] Batteries of various examples and comparative examples were prepared according to the above methods, and various performance parameters were measured. The results are shown in Tables 1 and 2 below.
[0269] Table 1
[0270] Table 2
[0271] The composite separators in Examples 1-16 all include a separator substrate and a conductive coating located on one side of the separator substrate. Comparisons between Example 1 and Comparative Example 1, and between Examples 2-16 and Comparative Example 2, show that the inclusion of a conductive coating on the composite separator helps reduce the overpotential of the battery and improve its cycling performance. It also reduces sodium dendrite formation and enhances the battery's safety and electrochemical performance.
[0272] Comparison of Examples 2-16 with Example 1 demonstrates that the composite separator also includes a ceramic coating on at least one side of the separator substrate, which helps improve the thermal shrinkage of the composite separator. When the ceramic coating is positioned between the separator substrate and the conductive coating, it can reduce battery self-discharge.
[0273] Comparison of Examples 2-6 with Comparative Example 2 shows that controlling the thickness of the conductive coating to 0.05 μm to 10 μm is beneficial for reducing the battery's overpotential, improving the battery's cycle performance, and alleviating the battery's sodium dendrite phenomenon. Comparison of Examples 2, 4-5 with Examples 3 and 6 shows that further controlling the thickness of the conductive coating to 0.5 μm to 5 μm can further significantly improve the battery's cycle performance.
[0274] From the comparison of Examples 2, 7 to 10 with Comparative Example 2, it can be seen that the conductive material in the conductive coating includes one or more of Super P, natural graphite, and carbon nanotubes, which are beneficial to reducing the overpotential of the battery, improving the cycle performance of the battery, and improving the sodium dendrites of the battery.
[0275] From the comparison of Examples 2, 11 to 14 and Comparative Example 2, it can be seen that controlling the thickness of the ceramic coating to 0.05 μm to 10 μm is beneficial to reducing the overpotential of the battery, improving the cycle performance of the battery, and improving the sodium dendrites of the battery.
[0276] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are merely examples, and any embodiments having substantially the same structure and effect as the technical concept within the scope of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the present application, any other embodiments that can be conceived by those skilled in the art and that combine some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A composite isolation membrane, characterized in that: The composite isolation film comprises an isolation film substrate and a conductive coating located on one side of the isolation film substrate.
2. The composite isolation membrane according to claim 1, characterized in that: The composite isolation film further comprises a ceramic coating located on at least one side of the isolation film substrate, wherein the ceramic coating is located between the isolation film substrate and the conductive coating; and / or The ceramic coating is located on a side of the isolation film substrate away from the conductive coating.
3. The composite isolation membrane according to claim 1 or 2, characterized in that: The thickness of the conductive coating is 0.05 μm to 10 μm, and can be optionally 0.5 μm to 5 μm.
4. The composite isolation membrane according to any one of claims 1 to 3, characterized in that: The surface density of the conductive coating is 0.01 mg / 1540.25 mm 2 ~15mg / 1540.25mm 2 , optional: 0.05mg / 1540.25mm 2 ~8mg / 1540.25mm 2 .
5. The composite isolation membrane according to any one of claims 1 to 4, characterized in that: The conductive coating includes a conductive material including at least one of a conductive carbon material and a conductive polymer.
6. The composite isolation membrane according to claim 5, characterized in that: The conductive carbon material includes at least one of a zero-dimensional carbon material, a one-dimensional carbon material and a two-dimensional carbon material, and optionally includes the one-dimensional carbon material.
7. The composite isolation membrane according to claim 6, characterized in that: The zero-dimensional carbon material includes at least one of acetylene black, Super P and Ketjen black; The one-dimensional carbon material comprises at least one of carbon nanofibers, carbon nanotubes, carbon nanohorns and carbon nanorods, and optionally comprises carbon nanotubes; The two-dimensional carbon material includes at least one of natural graphite and artificial graphite.
8. The composite isolation membrane according to any one of claims 2 to 7, characterized in that: The thickness of the ceramic coating is 0.05 μm to 10 μm, and can be optionally 0.5 μm to 3 μm.
9. The composite isolation membrane according to any one of claims 2 to 8, characterized in that: The surface density of the ceramic coating is 0.0001 mg / 1540.25 mm 2 ~0.05mg / 1540.25mm 2 , optional: 0.001mg / 1540.25mm 2 ~0.02mg / 1540.25mm 2 .
10. The composite isolation membrane according to any one of claims 2 to 9, characterized in that: The ceramic coating comprises an inorganic material, and the inorganic material comprises one or more of Al2O3, AlO(OH), SiO2, TiO2, MgO and CaO, and optionally comprises Al2O3.
11. The composite isolation membrane according to any one of claims 2 to 10, characterized in that: The conductive coating and / or the ceramic coating also includes a binder, which includes one or more of polyvinylidene fluoride, sodium hydroxymethyl cellulose, styrene-butadiene rubber, potassium carboxymethyl cellulose, polyacrylate, polyamide, polyimide, polyamide-imide, sodium alginate, polyvinyl alcohol, polytetrafluoroethylene and polyacrylonitrile, and optionally includes polyvinylidene fluoride.
12. The composite isolation membrane according to claim 11, characterized in that: The binder in the conductive coating is the same as the binder in the ceramic coating.
13. The composite isolation membrane according to claim 11 or 12, characterized in that: The mass ratio of the conductive material to the binder in the conductive coating is 4-49.
14. The composite isolation membrane according to any one of claims 11 to 13, characterized in that: The mass ratio of the inorganic material to the binder in the ceramic coating is 4-40.
15. The composite isolation membrane according to any one of claims 1 to 14, characterized in that: The isolation film substrate includes one or more of polyethylene, polypropylene, polyester, cellulose, polyimide, polyamide, spandex fiber and aramid fiber, and optionally includes polyethylene.
16. The composite isolation membrane according to any one of claims 2 to 15, characterized in that: The isolation film substrate includes polyethylene, the ceramic coating includes Al2O3, and the conductive coating includes carbon nanotubes.
17. The composite isolation membrane according to any one of claims 1 to 16, characterized in that: In any direction perpendicular to the thickness direction of the composite isolation film, the width of the conductive coating is less than the width of the isolation film substrate.
18. The composite isolation membrane according to any one of claims 1 to 17, characterized in that: In any direction perpendicular to the thickness direction of the composite isolation film, the width of the conductive coating is ≤ the width of the ceramic coating ≤ the width of the isolation film substrate.
19. A secondary battery, characterized in that: It comprises a negative electrode sheet and the composite separator according to any one of claims 1 to 18, wherein the conductive coating in the composite separator is located on the negative electrode sheet side.
20. The secondary battery according to claim 19, characterized in that: The secondary battery is a negative electrode-free sodium secondary battery.
21. The secondary battery according to claim 19 or 20, characterized in that: The negative electrode plate includes a negative electrode current collector. In any direction perpendicular to the thickness direction of the composite isolation film, the width of the conductive coating is ≤ the width of the negative electrode current collector < the width of the isolation film substrate.
22. The secondary battery according to any one of claims 19 to 21, characterized in that: The secondary battery further comprises a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode film layer located on a side of the positive electrode current collector facing the composite isolation membrane; In any direction perpendicular to the thickness direction of the composite separator, the width of the positive electrode film layer is less than the width of the conductive coating layer and less than the width of the separator substrate.
23. The secondary battery according to claim 22, characterized in that: In any direction perpendicular to the thickness direction of the composite isolation membrane, the difference between the width of the conductive coating and the width of the positive electrode film layer is 0 mm to 6 mm, the difference between the width of the negative electrode collector and the width of the conductive coating is 0 to 3 mm, and the difference between the width of the isolation membrane substrate and the width of the negative electrode collector is 1 mm to 9 mm.
24. The secondary battery according to any one of claims 19 to 23, characterized in that: The composite isolation film includes a ceramic coating, and in any direction perpendicular to the thickness direction of the composite isolation film, the width of the isolation film substrate is equal to the width of the ceramic coating.
25. An electrical device, characterized in that: A secondary battery comprising the secondary battery according to any one of claims 19 to 24.